Ligand Free One-Pot Synthesis of Pyrano[2,3-c]pyrazoles in Water Extract of Banana Peel (WEB): A Green Chemistry Approach - Dwivedi, Kartikey Dhar; Borah, Biplob; Chowhan, L. Raju (Frontiers in Chemistry, 2020)
Here, we have developed a novel, simple, efficient and green protocol for one-pot synthesis of pyrano[2,3-c]pyrazole by utilizing arylidene malononitrile and pyrazolone in Water Extract of Banana Peels (WEB) as a reaction medium at room temperature. This is a green and general synthetic protocol without using any toxic organic solvent, ligand, base which could be applicable for a wide range of substrate scope. This protocol has advantages of good to excellent yields, fast reactions, eco-friendly reaction conditions, easy isolation of the product without using column chromatography. The green chemistry matrices calculation like atom economy reaction, environmental factor, as well as process mass intensity indicates the eco-friendly nature of the protocol.